2013
DOI: 10.1016/j.enpol.2013.08.054
|View full text |Cite
|
Sign up to set email alerts
|

The impact of city-level permitting processes on residential photovoltaic installation prices and development times: An empirical analysis of solar systems in California cities

Abstract: Business process or "soft" costs account for well over 50% of the installed price of residential photovoltaic (PV) systems in the United States, so understanding these costs is crucial for identifying PV cost-reduction opportunities. Among these costs are those imposed by city-level permitting processes, which may add both expense and time to the PV development process. Building on previous research, this study evaluates the effect of city-level permitting processes on the installed price of residential PV sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 21 publications
5
31
1
Order By: Relevance
“…Two of these studies have examined the impact of local permitting processes on residential PV pricing. Dong and Wiser (2013) found that cities in California with the most-favorable permitting practices had installed prices $0.3/W to $0.8/W lower than in cities with the most-onerous practices. Examining a broader geographical footprint, Burkhardt et al (2014) found that variations in local permitting procedures lead to differences in average residential PV prices of approximately $0.2/W across jurisdictions; when considering variations not only in permitting practices, but also in other local regulatory procedures, price differences grew to $0.6/W to $0.9/W between the most-onerous and most-favorable jurisdictions.…”
Section: Text Box 4 Findings From Recent In-depth Analyses Of Pv Primentioning
confidence: 99%
“…Two of these studies have examined the impact of local permitting processes on residential PV pricing. Dong and Wiser (2013) found that cities in California with the most-favorable permitting practices had installed prices $0.3/W to $0.8/W lower than in cities with the most-onerous practices. Examining a broader geographical footprint, Burkhardt et al (2014) found that variations in local permitting procedures lead to differences in average residential PV prices of approximately $0.2/W across jurisdictions; when considering variations not only in permitting practices, but also in other local regulatory procedures, price differences grew to $0.6/W to $0.9/W between the most-onerous and most-favorable jurisdictions.…”
Section: Text Box 4 Findings From Recent In-depth Analyses Of Pv Primentioning
confidence: 99%
“…Due to its extensive nature, CSI data have been used as a proxy for PV deployment in California IOU territories in other published research (Dong & Wiser, 2013;Drury et al, 2012;Rothfeild, 2010). The data are biased toward established communities, because it does not include new construction, and do not represent "off-the-grid" systems that may be preferable to rural populations (Schelly, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Another growing body of research links reduced costs and permit processing times to increase PV adoption rates (Brown &Chandler, 2008;Burkhardt et al, 2015;Complete Solar, 2014;Dong & Wiser, 2013;Li & Yi, 2014). Confusing, costly, and time consuming permit applications can disincentivize residents who find bureaucratic processes prohibitive.…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations